The Memory of the Great War in two books for children – Polish and English perspectives - Krystyna Zabawa (Annales Universitatis Paedagogicae Cracoviensis. Studia Historicolitteraria, 2023)
Two books for children about the Great War will be discussed: Bohaterski miś [Heroic teddy bear] by Bronisława Ostrowska and Five Children on the Western Front by Kate Saunders. It will be a comparative analysis. The books differ in terms of national perspective (Polish and English), but also in the time of edition – just after the war and a hundred years later. Thus, Ostrowska’s memory about the war is her own memory, whereas Saunders’ writing can be called a postmemory narrative. The aim of the paper is to answer the questions: what is similar and what is different in the two selected children’s novels about the Great War? What are the ways of transmitting memory? What do the writers want to save for new generations?